IMAGE SCRAMBLING USING NON SINUSOIDAL TRANSFORM AND KEY BASED SCRAMBLING TECHNIQUE - Kekre, H.B.; Sarode, Tanuja; Halarnkar, Pallavi; Mazumder, Debkanya (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Nowadays Digital Images find a lot of applications almost in all the fields, for e.g. Information Hiding. Security of these images is very important. Image encryption is one method of providing security to digital images. In this paper we have proposed a method for Image scrambling which is based on a combination of spatial and frequency domain.Â Four different Non sinusoidal transforms, Walsh , Slant ,Kekre and Haar were used. Three different types i.e Row , Column and Full Transforms of these four transforms were applied for Image scrambling , out of these four Kekre Transform gave the best result